The Impacts of Spatial Interaction on Agricultural Productivity and Average Income: A Case of Vietnam - Bac Truong Cong; Tran Quang Van (Borong Newinera Publisher, 2021)
Agricultural productivity plays a crucial role in sustainable development while income is one of the most critical indicators that manifest the living standards; therefore, both of these aspects have attracted much attention from the national level to the provincial level. Yet, for various reasons, the importance of regional linkages, especially spatial interaction in the analysis of agricultural productivity and the average income, is not recognized and thus ignored in economic policies. Taking Vietnam as the study area, this paper examines the impact of spatial interaction between metropolises and provinces on agricultural productivity and income per capita of provinces. In order to evaluate the impacts, this paper uses a gravity model to estimate the spatial interaction then panel data analysis is employed to interpret the influences. The data used in this study is collected from the General Statistics Office of Vietnam in the period from 2015-2018. The results show a positive correlation between spatial interaction between metropolis and provinces to provincial change, including agricultural productivity and average income. As such, stronger linkages with metropolises through improving transportation systems could enhance agricultural productivity and income in the province.